Efficiency of carbon dioxide uptake by different concentration of a marine microalgae, chlorella vulgaris under laboratory condition - Kassim, Zaleha; Ibrahim, Khairatus Shyahirah; Yunus, Kamaruzzaman (2019)
Green microalgae play an important role in carbon fixation in a marine ecosystem. Nonetheless, the factors involve in the process could be varied and affected by other environmental condition. A study was carried out to determine the relationship between concentration of Chlorella vulgaris and carbon dioxide (CO2) absorption by taking pH readings, once in three hours for 24 hours. The samples were supplied with different CO2 flow rate. C. vulgaris was cultured in autoclaved culture tubes for a few days with 25 – 30 ppt of seawater, NPK fertilizer and the condition was maintained at 23 – 25 °C. All dilutions of C. vulgaris under different CO2 supply showed increasing trends in pH readings within 24 hours. However, there is no significant difference observed (p>0.05) in all samples for the increment of pH from 0 hour to 24 hours. The growth of C. vulgaris under different CO2 was also observed in biomass productivity and CO2 fixation rate. The highest biomass productivity was 0.2257 g L-1 d-1 represented by 3.6755×105 cells/mL of C. vulgaris under CO2 flow rate of 17 L/min. The highest CO2 fixation rate was observed in 1.1175 × 106 cells/mL of C. vulgaris under natural condition where CO2 supplied with 0.0700 g L-1 d-1. Pearson’s correlation coefficient showed that both biomass productivity and CO2 fixation rate have strong correlation between them but have no relationship with dilutions of C. vulgaris and different CO2 conditions. Longer period of CO2 exposure could give different result. Further investigation on the effect of concentrations of C. vulgaris and CO2 in relation to period of exposure would give more information on the fixation of CO2 by microalgae.